In silico analysis and 3D structure prediction of a chitinase from psychrophilic yeast Glaciozyma antarctica PI12 - Yusof N.Y.,; Firdaus-Raih M.,; Mahadi N.M.,; Illias R.M.,; Abu Bakar F.D.,; Murad A.M.A., (Penerbit Universiti Kebangsaan Malaysia, 2017)
Chitinases are a group of glycosyl hydrolases that are essential to recycle chitin presence in nature. The aim of this work is to characterise the sequence of a chitinase isolated from a psychrophilic yeast, Glaciozyma antarctica PI12 and to predict and analyse the 3-dimensional protein structure. The cDNA for the G. antarctica chitinase gene, GaCHT43, with a length of 1,176 bp was reverse transcribed from mRNA, cloned and sequenced. The gene encodes a mature protein of 391 amino acids with an expected molecular weight of 43 kDa. Sequence analysis showed that GaCh43 has high similarity to the endochitinase family 18 proteins of other fungi. A three-dimensional (3D) model of GaCht43 was built by homology modelling with Aspergillus fumigatus chitinase (1W9P) as the template. Validation analysis via PROCHECK, VERIFY3D and ERRAT showed that the GaCht43 model surpassed the quality requirements and was accepted for further analysis. GaCht43 contained chitinase conserved regions, SxGG and DxxDxDxE that are required in the catalytic mechanism. Analysis of the GaCht43 structure showed the presence of extra loop regions compared to mesophilic chitinases, which might contribute to the flexibility of the protein.